My mini book of colours (Say Publishing Karachi, 2011)
This vibrant mini book introduces young children to the colorful world around them. Through bright illustrations and simple text, children will learn to identify and name a variety of colors. Each page features a different color, accompanied by objects that showcase that color. This engaging book aims to stimulate visual perception and language development, while fostering a sense of wonder and creativity.